EVALUASI PENERAPAN HIGIENE SANITASI DI HOTEL SWISSBELINN BALIKPAPAN - Setyawati, Nur Falah; Maslina, Maslina; Wahyuni, Sri; Aprillian, Andini Ayu (IDENTIFIKASI, 2022)
Occupational safety and health is related to food safety because food safety regulates sanitation hygiene, one of which is food handlers. Based on PERMENKES No 1096/2011, food safety is a condition and effort needed to prevent food from being contaminated by biological, chemical, and other objects that can interfere, harm and endanger human health. Humans are one of the agents causing the entry of contaminants into food (Irianto, 2007). Food handlers are people who directly manage food. The purpose of this study was to evaluate the application of hygiene and sanitation to food handlers at the Swissbelinn hotel, Balikpapan. This research design uses descriptive qualitative method. Informants in this study were food handlers who were in the kitchen department of the swssbelinn hotel, Balikpapan. Data was collected by means of interviews, observation, data documentation, and taking pictures. Based on the results of interviews with 10 informants, it can be concluded that 6 of the food handlers applied sanitary hygiene in accordance with PERMENKES No. 1096 of 2011, while 3 of them had not applied sanitation hygiene while working and did not comply with PERMENKES No. 1096 of 2011. while working, that based on interviews and observations of special handlers, informants 2,3,4,7.9 always guarantee and implement food safety when processing food and work by implementing sanitation hygiene in accordance with PERMENKES No 1096 of 2011. Meanwhile, informants 5,6, 8 do not have sanitation hygiene certification and do not understand about food safety.